Association of left ventricular structure and function with peripheral blood mitochondrial DNA content in a general population. (1st July 2016) - Knez, Judita; Cauwenberghs, Nicholas; Thijs, Lutgarde; Winckelmans, Ellen; Brguljan-Hitij, Jana; Yang, Wen-Yi; Staessen, Jan A.; Nawrot, Tim S.; Kuznetsova, Tatiana
Abstract: Background/objectives: mtDNA content might be an important biomarker in heart disease prediction and to date no population studies are available on the association of mtDNA content with cardiac structure and function. We, therefore, investigated in a general population in cross-sectional and longitudinal studies whether echocardiographic indexes of LV structure and function are associated with mtDNA content measured in peripheral blood cells. Methods: At baseline we performed echocardiography in 701 randomly selected individuals (50.9% women, mean age, 53.2 years) from a Flemish population. Relative mtDNA copy number compared to nuclear DNA was measured by quantitative real-time PCR in peripheral blood cells. Results: With adjustments applied, we observed significant inverse association of LV diastolic and systolic diameters ( P ≤ 0.028) and volumes ( P = 0.013) with mtDNA content. Moreover, for a 1-SD increment in mtDNA (0.37), we found an increase in Tissue Doppler s′ velocity by 0.093 cm/s ( P = 0.019) and a decrease in E/e′ ratio by 0.18 ( P = 0.008). In 223 subjects with available echocardiography and mtDNA content at baseline and follow-up, we observed that higher baseline mtDNA content was associated with less increase in 2D LV diastolic volume ( P = 0.0003), M-mode LV diameter ( P = 0.046) and LV mass ( P = 0.003) during the follow-up period. Conclusions: In the general population, higher mtDNA content was associated with smaller LV diastolic and systolic diameters and volumes and better LV systolic and diastolic function. Moreover, we observed that baseline mtDNA content was a significant predictor of longitudinal changes of LV diastolic volume and dimension, and LV mass.